Pemenuhan Hak Korban Jarimah Menurut Qanun Nomor 16 Tahun 2014 Tentang Hukum Jinayat - Airi Safrijal; Nurhafifah Nurhafifah; Nora Mia Azmi (Indonesian Journal Publisher, 2026)
Restitution is a form of fulfillment of victims’ rights as part of uqubat aimed at protecting the interests of victims, particularly victims of rape crimes. This study aims to analyze the legal regulation of restitution for victims of rape under Aceh Qanun Number 6 of 2014 concerning Jinayat Law and Supreme Court Regulation Number 1 of 2022, as well as to examine the obstacles in fulfilling restitution rights for victims of criminal offenses. The research method employed is normative legal research using a library research approach by examining statutory regulations, legal doctrines, books, journals, and other relevant legal materials. The results of the study indicate that restitution for victims of rape has been normatively regulated in Aceh Qanun Number 6 of 2014 concerning Jinayat Law and Supreme Court Regulation Number 1 of 2022 concerning the Procedures for the Settlement of Applications and the Provision of Restitution and Compensation to Victims of Crimes. Restitution constitutes the right of the victim, the obligation of which is imposed on the perpetrator or the perpetrator’s parents and may be granted upon the victim’s request to the judge during court proceedings. However, the fulfillment of restitution rights faces obstacles, particularly the lack of awareness among victims, their families, and the community regarding the existence of restitution rights as regulated in the Qanun and the Supreme Court Regulation. Therefore, it is concluded that greater efforts are required from the government and relevant institutions to conduct legal socialization and enhance public awareness to ensure the effective fulfillment of restitution rights for victims of criminal offenses..